Schisandrin B-mediated TH17 cell differentiation attenuates bowel inflammation. (April 2021) - Ma, Zeyu; Xu, Gang; Shen, Yingying; Hu, Shufang; Lin, Xia; Zhou, Jun; Zhao, Wei; Liu, Jian; Wang, Jiaoli; Guo, Jufeng
Graphical abstract: The transcription factor STAT3 facilitates naïve CD4 + T cells differentiation into TH 17 cells. While, Sch B decreases IL-17A production of CD4 + T cells by targeting STAT3 in vitro and in vivo . TH 17 cells promotes the pathogenesis of IBD. Thus, Sch B alleviates IBD through decreasing TH 17 cells. Highlights: Schisandrin B alleviates DSS-induced acute and chronic colitis. Schisandrin B alleviates CD4 + CD45RB high T cell-induced colitis. Schisandrin B protects mice from colitis by targeting TH 17 cells. Schisandrin B decreases TH 17 cell differentiation in a STAT3 dependent manner. Schisandrin B inhibited human TH 17 cell differentiation in vitro . Abstract: Schisandrin B (Sch B) is the major active constituent of the traditional Chinese medicine Schisandra chinensis and has anti-inflammatory activity, but the target of Sch B remains unclear. T helper 17 (TH 17) cells have been involved in the pathogenesis of many autoimmune and inflammatory diseases. Here, we showed that Sch B could decrease IL-17A production of CD4 + T cells by targeting STAT3 in vitro . Importantly, Sch B has therapeutic effects on DSS-induced acute and chronic colitis, CD4 + CD45RB high T cell-induced colitis. Furthermore, we identified TH 17 cells as the direct target of Sch B for mediating its anti-inflammatory activity. Sch B could serve as a lead for developing new therapeutics against TH 17 cells or IL-17A cytokine-driven diseases.